Persistence of rubella and mumps antibodies, following changes in the recommended age for the second dose of MMR vaccine in Portugal - Gonçalves, G. (2017)
In Portugal, the recommended age for the second dose of MMR (MMR2) was changed from 10-13 years to 5-6 years for those born in 1994 and afterwards. This study aimed to assess if MMR schedule and time elapsed from the last dose are associated with the concentration of rubella and mumps IgG antibodies. Three Portuguese birth cohorts (convenience samples) were selected for this study (66, 59 and 41 participants born respectively in 1990-1993, 1994-1995 and 2001-2003). Geometric mean concentrations (GMC) for mumps IgG were respectively 36, 30 and 38 RU/ml (P = 0·236) and for rubella IgG were 18, 20 and 17 IU/ml (P = 0·641). For both specific antibodies, no differences were observed with time since MMR2. Receiving MMR2 at 5-6 or 10-13 years was not associated with concentration of both antibodies. The GMC of rubella IgG was lower in males (P = 0·029). Taking into account previous evidence and the logistics needed to change vaccination schedules, it seems reasonable that sustaining very high coverage with two doses of MMR is currently the most pragmatic way to control mumps and rubella rather than any changes to the schedule.